Maternal Death and Isolated Left Ventricular NonCompaction Cardiomyopathy - R., Razuin; M.N., Shahidan; K., Thanikasalam (IIUM Medical Journal Malaysia, 2017)
Left ventricular non-compaction cardiomyopathy (LVNC) is a rare congenital cardiomyopathy, which is characterized by hypertrabeculations and deep recesses of the left ventricle. A patient could be asymptomatic or presented with common manifestations, including reduced systolic function, arrhythmia, thromboembolic events and heart failure. The rarity of the condition as well as lack of proper assessment has probably led to this condition to be largely underdiagnosed or unrecognized. A 23-year-old lady had collapsed at home thirty one days after delivering her first child. She had a history of goitre diagnosed a year ago and noted to be fairly well throughout the pregnancy. Post mortem findings showed increased trabeculations of the left ventricle. Further history was obtained after the procedure, revealing symptoms such as syncopal attacks and bilateral lower limb weakness dated back as far as five years prior to her sudden demise. These features were in keeping with hypotension hypoperfusion effects resulted from reduced systolic function and decreased ejection fraction, as a result of left ventricular dysfunction. While LVNC remains a rare type of disease, we would like to highlight the importance of a good anamnesis. It may help to uncover some uncommon pathology such as this heart disease, thus warranting an appropriate cardiac imaging to be engaged to clinch the primary diagnosis.